2016
DOI: 10.1007/s00247-016-3623-x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective detection of cortical dysplasia on clinical MRI in pediatric intractable epilepsy

Abstract: Awareness of current classification schemes of cortical dysplasia and image review in the context of a multidisciplinary conference can lead to improved MRI detection of cortical dysplasia in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
7
0
3
Order By: Relevance
“…The patient's clinical history and seizure semiology are presented along with clinically validated tools of video EEG, MRI, PET, and ictal SPECT [8]. Multiple pediatric studies have reported that degree of concordance among the studies correlates with postoperative outcomes [9][10][11]. From the available data, hypotheses of involved networks and spread patterns are generated.…”
Section: One Institution's Approach To Patient Management Conferencementioning
confidence: 99%
See 2 more Smart Citations
“…The patient's clinical history and seizure semiology are presented along with clinically validated tools of video EEG, MRI, PET, and ictal SPECT [8]. Multiple pediatric studies have reported that degree of concordance among the studies correlates with postoperative outcomes [9][10][11]. From the available data, hypotheses of involved networks and spread patterns are generated.…”
Section: One Institution's Approach To Patient Management Conferencementioning
confidence: 99%
“…In some cases, surgery may be recommended to patients initially not thought to be surgical candidates (case example 1). Radhakrishnan et al analyzed the benefit of retrospective unblinded review of reportedly normal preoperative MRIs of children with medically intractable epilepsy and histopathology consistent with cortical dysplasia [9]. In their study, 18/78 children had overlooked MRI findings, and 72% of these (13/18) were identified prospectively at PMC.…”
Section: One Institution's Approach To Patient Management Conferencementioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic resonance imaging (MRI) detection of FCD is fundamental for surgical planning and leads to better outcomes 3,4 . Unfortunately, a significant number of FCDs may be overlooked by MRI 5–8 . MAP is a voxel‐based morphometric analysis program that quantifies interindividual variability on T1‐ and T2‐weighted volumetric MRI.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Unfortunately, a significant number of FCDs may be overlooked by MRI. [5][6][7][8] MAP is a voxel-based morphometric analysis program that quantifies interindividual variability on T1-and T2-weighted volumetric MRI. Wang et al recently published a study emphasizing the importance of MAP in presurgical evaluation of drug-resistant focal epilepsy in children with apparently normal MRI using an agespecific template created with controls as young as 3 years of age.…”
Section: Introductionmentioning
confidence: 99%